Pengaruh Store Atmosphere, Display Product, Dan Hedonic Shopping Motivation Terhadap Impulse Buying Pada Konsumen Alfamart Di Kabupaten Boyolali - Farihin, Nadhif Rahman; Kuswati, Rini (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The development of the retail industry in Indonesia has experienced significant growth in recent decades. The presence of various modern retail chains such as Alfamart, Indomaret, and other minimarkets has changed people's consumption patterns. "Alfamart, as one of the largest retail chains in Indonesia, plays an important role in providing people's daily needs at affordable prices and easily accessible locations. In the context of increasingly fierce competition, it is important for Alfamart to understand consumer behavior in order to increase sales and maintain customer loyalty". This study uses a quantitative method with a survey approach to test the influence of store atmosphere, display product, and hedonic shopping motivation on impulse buying among Alfamart consumers in Boyolali Regency